A Novel Bacterial Protease Inhibitor Adjuvant in RBD-Based COVID-19 Vaccine Formulations Containing Alum Increases Neutralizing Antibodies, Specific Germinal Center B Cells and Confers Protection Against SARS-CoV-2 Infection in Mice - Coria, Lorena M.; Saposnik, Lucas M.; Pueblas Castro, Celeste; Castro, Eliana F.; Bruno, Laura A.; Stone, William B.; Pérez, Paula S.; Darriba, Maria Laura; Chemes, Lucia B.; Alcain, Julieta; Mazzitelli, Ignacio; Varese, Augusto; et al. (Frontiers in Immunology, 2022)
In this work we evaluated recombinant receptor binding domain (RBD) based vaccine formulation prototypes with potential for further clinical development. We assessed different formulations containing RBD plus Alum, AddaS03, AddaVax or the combination of Alum and U-Omp19: a novel Brucella spp. protease inhibitor vaccine adjuvant. Results show that the vaccine formulation composed of U-Omp19 and Alum as adjuvants have a better performance: it significantly increased mucosal and systemic neutralizing antibodies in comparison to antigen plus Alum, AddaVax or AddaS03. Antibodies induced with the formulation containing U-Omp19 and Alum not only increased their neutralization capacity against the ancestral virus but also cross neutralized alpha, lambda and gamma variants with similar potency. Also, addition of U-Omp19 to Alum vaccine formulation increased the frequency of RBD-specific geminal center B cells and plasmablasts. Additionally, U-Omp19+Alum formulation induced RBD-specific Th1 and CD8+ T cell responses in spleens and lungs. Finally, this vaccine formulation conferred protection against an intranasal SARS-CoV-2 challenge of K18-hACE2 mice.